Wellness Promotion Courses in University Settings: A Review of the Outcome Research - James Beauchemin; Todd Gibbs; Paul Granello (The Ohio State University Libraries, 2018)
Background: Improving college student wellness continues to be a challenge due to concerns related to lifestyle, unhealthy behavior, and lack of accessible supports, often resulting in poor academic performance and high drop-out rates. As a result there has been an increase in wellness-promoting academic courses across colleges and universities with the goal of helping students to establish healthy lifestyle behaviors. Aim: This article critically reviews the existing literature related to college courses designed to promote student wellness. Methods: This scoping review examines research related to courses designed to improve wellness within the college student population between the years 2000-2017 using multiple electronic databases. Results: Review findings include a lack of rigorous research designs, lack of integration of evidence-based models of wellness, challenges associated with consensus conceptualizations of wellness, fidelity, and replicability of wellness-related courses. Conclusions: Wellness as an emerging paradigm continues to gain attention in the literature, particularly related to college students. However, there is a need for more rigorous study designs, examination of mechanisms of change, and consensus related to conceptualizations of wellness and component definitions to inform wellness-promotion efforts, and ultimately support health-enhancing change within the existing lifestyle culture on college campuses.